RITUAL PERFORMANCE AS CULTURAL ARCHIVE: A STUDY OF MOHAN-DEODHAI-BAILUNG CEREMONIES IN ASSAM. - Phukan, Nakul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper investigates how the ritual performances of the Mohan-Deodhai-Bailung community of Assam function as embodied archives that preserve and transmit cultural memory and communal identity. As priest-healers deeply rooted in indigenous epistemologies, the Mohan, Deodhai, and Bailung perform ceremonial practices that not only mediate between the natural and spiritual realms but also encode historical consciousness and ancestral narratives. Drawing on Richard Schechner’s theory of performance as restored behaviour and Jan Assmann’s theory of cultural memory, the study situates these ritual actions as dynamic, performative texts through which oral knowledge, cosmology, and social cohesion are enacted and remembered. Based on ethnographic observation and cultural performance analysis, the paper reveals how gesture, chant, sacred objects, and spatial arrangements are employed to transmit indigenous knowledge across generations. In doing so, it argues that the ceremonial practices of the Mohan-Deodhai-Bailung are not static traditions but evolving cultural repositories—resilient and responsive to external pressures while safeguarding a unique worldview. These rituals emerge as critical to understanding the role of performance in sustaining identity, healing memory, and affirming indigenous sovereignty in contemporary Assam.